Post-Structuralism of Hadith: A Critical Study Of The Logocentrism of Hadith Reason According To J. Derrida's Deconstruction - Irwansya; Taufikquraman (Taqaddumi: Journal of Quran and Hadith Studies, 2023)
The dynamics of the struggle of contemporary hadith understanding methodology is one of the interesting phenomena to be studied as the conditions of culture and human civilization accelerate. The search for absolute meaning is impossible. By Deconstruction the rules that envelop Logocentrism can be revealed. Using a deconstruction approach, we can uncover how logocentrism affects the way we understand and interpret hadith, and criticize how such logocentrism might limit our understanding of hadith. The research method is qualitative with a descriptive approach to deco-construction analysis. The results of this study show that it is this kind of Model of Reason that makes hadith reasoning dogmatic, Qathi’, closing itself off from interdisciplinary science and repeatedly failing to hack into the problems of the times. It is also on this basis that the development of the hadith understanding model has stagnated and the methodology is poor. That way, hadith reasoning is easily monopolized by certain madhabs that are full of interests. The crystallization of reason is incapable of dialoguing hadith with reality. It therefore took the deconstruction of Jacques Derrida to dismantle the discourse of logocentrism of hadith reasoning. This deconstruction of hadith reasoning is carried out to see and distinguish universal aspects of Islam and aspects of Islam that are local and temporal, so as not to narrow reason to project hadith as instructions that apply throughout the ages.